World Trade Organisation case law on agricultural matters. Selected issues - Srogosz, Tomasz (Przegląd Prawa Rolnego, 2026)
This study aims to determine the role of World Trade Organisation (WTO) case law in shaping the agricultural policies of the EU and its member states, using Poland as an example. First, the author outlines the WTO dispute settlement system, including the current crisis in its functioning. The author then presents selected rulings involving the EU and Poland relating to: meat and meat products (hormones); the import, sale and distribution system for bananas; sugar export subsidies; authorisation and marketing measures for biotechnology products; sugar import safeguard measures; additional duties on Polish pork imports; and measures concerning Ukrainian agricultural products. The author concludes that the EU and its Member States do not always act in accordance with the recommendations of panel and Appellate Body reports. Furthermore, the procedures aimed at holding states and the EU to account within the WTO dispute settlement system are too lengthy, and the paralysis of the Appellate Body has seriously undermined the effectiveness of this system. Nevertheless, the author emphasises the WTO dispute settlement system’s positive contribution to the liberalisation of agricultural trade, while also highlighting its impact on the development of agricultural law and policy at the national and EU levels.